Damage to 'Cabernet Sauvignon' after late frost in the Southern Brazilian highlands - Marcon Filho J.L.* (2016)
Occurrence of frost after budburst may cause damage to the grapevine young shoots, leading to significant losses. However, pruning shoots affected by low temperatures in cultivars that have fertile secondary buds can be an option to reduce losses in viticulture. On September 26, 2012, part of a block of the vineyard studied had shoots damaged by frost due to the failure of preventative systems. Consequently, the objective of this study was to quantify the damage caused by spring frost on vines grown in high-altitude regions of southern Brazil. The experiment was conducted during the 2013 vintage in commercial vineyards, with 'Cabernet Sauvignon' grafted on Paulsen 1103, grown on a Y-shaped trellis system, spaced at 3.0×1.5 m. The treatments consisted of damaged plants, which received a second pruning after the occurrence of frost and plants that were not affected by low temperatures. Damage from freezing temperatures caused an 85% reduction in productivity. Cluster length and compactness index as well as berry number, mass and size were higher in vines without frost damage. However, no differences were observed for the soluble solids, acidity, pH, polyphenols and colour of the grapes between treatments. We conclude that budburst vines which experience frost damage see a loss in the yield. Also a second pruning after frost can minimize the loss caused by frost on 'Cabernet Sauvignon' wine grape grown in the southern Brazilian highlands.